Homicide Disguised By Suicide: A Rare Case Report - Waghmare, Sushim; Phalke, Balaji; Kamble, Vijay; Zine , K U (Journal of Indian Academy of Forensic Medicine, 2015)
Violent asphyxial deaths are of common occurrence and constitute large group in medico-legal  autopsies. Death due to constriction of neck may broadly result due to hanging, strangulation with  ligature material or manual strangulation i.e. throttling. Sometimes due to external post-mortem  appearance of the ligature marks on neck, it becomes difficult for the autopsy surgeon to clearly state  whether the constriction of neck is homicidal or suicidal in nature. So in these cases, the expertise & high  index of suspicion by “an expert forensic surgeon” is warranted to unmask the murder in disguise. Here  we are presenting a case of man who supposed to hanged himself with the help of a nylon rope as per  statement given by his wife and fabricating a scene of incidence as hanging and also the preliminary  investigation by police as narrated before autopsy both were same. But a meticulous autopsy revealed  that, cause of death is throttling and ultimately police registered a criminal case of murder against the  alleged accused i.e. on his wife.
Keywords: Homicide; Asphyxia; Throttling; Autopsy; Ligature mark